A single amino acid determines position specificity of an Arabidopsis thaliana CCoAOMT‐like O‐methyltransferase. Issue 6 (14th February 2013) - Wils, Christopher Ralf; Brandt, Wolfgang; Manke, Kerstin; Vogt, Thomas
Abstract : Caffeoyl‐coenzyme A O ‐methyltransferase (CCoAOMT)‐like proteins from plants display a conserved position specificity towards the meta ‐position of aromatic vicinal dihydroxy groups, consistent with the methylation pattern observed in vivo. A CCoAOMT‐like enzyme identified from Arabidopsis thaliana encoded by the gene At4g26220 shows a strong preference for methylating the para position of flavanones and dihydroflavonols, whereas flavones and flavonols are methylated in the meta‐ position. Sequence alignments and homology modelling identified several unique amino acids compared to motifs of other CCoAOMT‐like enzymes. Mutation of a single glycine, G46 towards a tyrosine was sufficient for a reversal of the unusual para ‐ back to meta ‐ O ‐methylation of flavanones and dihydroflavonols. Abstract : ► An Arabidopsis CCoAOMT‐like methyltransferase displays para ‐ O ‐methylating activity with flavanones. ► Molecular modelling predicts candidate amino acids in the active site. ► The position specificity is reversed by a single amino acid exchange.